The effect of safety modifications on head kinematics experienced during common skills in women`s artistic gymnastics - Pritchard, N. S.; Brandt, K. M.; Bullock, G. S.; Kruse, D. W.; Miles, C. M.; Moore, J. B.; Sitzel, J. D.; Urban, J. E. (Journal of Sports Sciences, 2024)
The objective of this study was to evaluate the effect of skill modifications on head motion experienced during women`s artistic gymnastics skills. Nine gymnasts (four beginner and five advanced) completed three trials of up to 24 skill progressions, each consisting of a skill and two progressive safety modifications. Gymnasts were instrumented with mouthpiece sensors embedded with an accelerometer and gyroscope collecting motion data at 200, 300, and 500 Hz during each skill performance. Peak-to-peak linear and rotational kinematics during contact phases and peak rotational kinematics during non-contact phases were computed. A mixed-effects model was used to compare differences in modification status nested within skill categories. Timer skills (i.e. drills that simulate performance of a gymnastics skill) resulted in the highest median ?LA and ?RA of all skill categories, and 132 skill performances exceeded 10 g ?LA during a contact phase. Modifications were associated with significant reductions in head kinematics during contact phases of timers, floor skills, bar releases, and vault skills. Gymnasts can be exposed to direct and indirect head accelerations at magnitudes consistent with other youth contact sports, and common safety modifications may be effective at reducing head motion during contact and non-contact phases of gymnastics skills.